Análisis financiero de la empresa Inpaecsa y su efecto en los resultados - Suarez Verdezoto, Milton Omar (2019)
The industry Papelera Ecuatoriana S.A. which belongs to the industrial sector is mainly engaged in the manufacture of pulp and also produces paper and then converts them into processed, semi-finished and finished products. After analyzing the financial statements for the 2017-2018 period, a decrease in its net results is observed in consideration to the year 2017 due to the significant changes that have existed in the level of its costs. The last period, presented an increase in its sales costs due to the acquisition of its raw material by FAMILY GROUP